Thermoelectric performance of PbSnTeSe high-entropy alloys - Zhao Fan; Hui Wang; Yuan Wu; Xiongjun Liu; Zhaoping Lu (Materials Research Letters, 2017)
In our study, we designed the PbSnTeSe high-entropy alloy (HEA) and investigated its microstructure and thermoelectric properties. It was found that the PbSnTeSe HEA has a simple face-centered cubic structure and possesses quite low lattice thermal conductivity at low temperatures, which could be ascribed to the strong phonon scattering due to its severe lattice-distortion. Minor additions of La not only enhanced both Seebeck coefficient and electrical conductivity at high temperatures, but also suppressed the bipolar effect to some degree. Our results indicate that the HEA concept could be applied for developing promising thermoelectric materials, which merits further investigation.